2021
DOI: 10.1063/5.0037104
|View full text |Cite
|
Sign up to set email alerts
|

Aperiodic optical coatings for neutral-color semi-transparent organic photovoltaics

Abstract: Semi-transparent organic photovoltaics (ST-OPVs) have the potential for integration with windows for ubiquitous power generating applications. Typically, such applications require that ST-OPVs be neutrally transparent across the visible and exhibit both a high average photopic transmittance (APT) and color rendering index, as well as iso-energetic chromaticity coordinates. In this work, we demonstrate the design and use of optical coatings to achieve ST-OPVs with a neutral visible transmittance of APT = 50%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Li et al placed a DBR behind a thin film Ag back electrode and demonstrated a concomitant reduction in the AVT upon the use of a DBR due to an observed shift of the device's transmission maximum to the response maximum of the human eye (555 nm) [106]. Similarly, aperiodic thin film coatings for ST-OPVs can help to achieve high neutral transmittance and an increased PCE by flattening the transmission spectrum and reflecting near IR photons [107].…”
Section: Current Performance and Strategies To Increase Luementioning
confidence: 99%
“…Li et al placed a DBR behind a thin film Ag back electrode and demonstrated a concomitant reduction in the AVT upon the use of a DBR due to an observed shift of the device's transmission maximum to the response maximum of the human eye (555 nm) [106]. Similarly, aperiodic thin film coatings for ST-OPVs can help to achieve high neutral transmittance and an increased PCE by flattening the transmission spectrum and reflecting near IR photons [107].…”
Section: Current Performance and Strategies To Increase Luementioning
confidence: 99%
“…The intrinsic stability of organic photovoltaics (OPVs) has been demonstrated by Y. Li et al 1 . By replacing the opaque contact on the distal side of the device with a transparent one such as indium tin oxide (ITO) and with proper optical engineering 2,3 , neutrally colored semi-transparent organic photovoltaics (ST-OPVs) can be achieved. The optical design of the ST-OPV reported here enables it to block out ultraviolet (UV) photons and harvest near infrared (NIR) ones, making the device suitable to replace passive windows.…”
Section: Introductionmentioning
confidence: 99%
“…22–24 Table S1† demonstrates the comprehensive investigations on performances of state-of-the-art single-junction ST-SCs. 17,25–34 These attempts open a path to develop single-junction ST-SCs with balanced photovoltaic performances and optical transmittance. However, single-junction solar cells still suffer from the Shockley–Queisser (S–Q) limitation and color-fidelity, and consequently, it is difficult to further improve their device efficiency at a relatively high AVT.…”
Section: Introductionmentioning
confidence: 99%